Non traumatic lower extremity amputations in younger patients: an 11‐year retrospective study. Issue 1 (13th February 2012) - Chin, Jessica WS; Teague, Laura; McLaren, Ann‐Marie; Mahoney, James L
<x xml:space="preserve">Abstract</x> The purpose of this study was to assess morbidity and mortality in patients undergoing non traumatic lower extremity amputations ≤65 years to identify the specific needs of these younger patients. A retrospective study was conducted to determine the demographics, comorbidity and mortality with below‐knee amputations and above‐knee amputations from 1998 to 2008. A total of 203 amputations were performed on 176 patients who were ≤65 years. Major comorbidities and associated physical findings were peripheral vascular disease, diabetes, pain, gangrene, hypertension, ulcer, local wound infection and hypercholesterolemia. Compared to patients who were not deceased post‐amputation, those deceased had a higher prevalence of diabetes, renal failure, coronary artery disease (CAD) and sepsis. Significant predictors of mortality were renal failure (hazard ratio [HR] = 4·19; 95% CI 1·96–8·93), CAD (HR = 3·33; 95% CI 1·42–7·81) and amputation site (above‐knee) (HR = 3·26; 95% CI 1·51–7·04). This study showed that younger patients may benefit from an interdisciplinary approach in treating local foot ulcers aggressively and optimising their cardiovascular, renal and diabetic risk factors.